2009
DOI: 10.1542/peds.2008-0313
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Genetic Predisposition to Patent Ductus Arteriosus in Preterm Infants

Abstract: Patent ductus arteriosus (PDA) is a common morbidity associated with preterm birth. The incidence of PDA increases with decreasing gestational age to about 70% in infants born at 25 weeks gestation. Although medical treatment with non-steroidal anti-inflammatory drugs (NSAIDs) is used to close the ductus arteriosus, approximately 30% of infants with a PDA do not respond to pharmacologic attempts at closure. We investigated whether single nucleotide polymorphisms (SNPs) in genes that regulate smooth muscle cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
5
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 30 publications
(34 reference statements)
1
65
5
3
Order By: Relevance
“…Recently, identification of specific genes for PDA has been reported [9,10,11,12,13,21]. Genes that interfere with remodeling of vascular smooth muscle cells of the ductal media are thought to lead to PDA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, identification of specific genes for PDA has been reported [9,10,11,12,13,21]. Genes that interfere with remodeling of vascular smooth muscle cells of the ductal media are thought to lead to PDA.…”
Section: Discussionmentioning
confidence: 99%
“…Treszl et al [21] reported polymorphism in the AGTR1 gene (rs5186), which is related to angiotensin II-related vasoconstriction that influences PDA closure with indomethacin. Dagle et al [13] reported a significant association of alleles in the TFAP2B and EPAS1 genes (both found to be expressed in the smooth muscle cells of mouse ductus arteriosus, playing key roles in ductal closure), with subsequent need for surgical ligation in preterm infants. Because PDA usually occurs sporadically, it has not been regarded as a typical genetic disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed ductal closure is related to prematurity and exaggerated by comorbidities such as respiratory distress syndrome and sepsis. A genetic basis for ductal patency has also been suggested by mutations and polymorphisms within genes interfering with remodeling of vascular smooth muscle cells of ductal media [15].…”
Section: Morphogenesismentioning
confidence: 99%
“…2 This may be due to many factors including decreased tone due to presence of immature smooth muscle myosin isoforms and impairment of calcium entry through L-type calcium channels, increased sensitivity to prostaglandin E2 (PGE 2 ) and nitric oxide, or increased levels of PGE 2 . [3][4][5] The clinical consequences of a patent ductus arteriosus (PDA) are related to the degree of left-to-right shunt through the PDA with its associated change in blood flow to the lungs, kidneys, and intestines. 2 Preterm infants of <30 weeks gestation with severe respiratory distress have a 65% incidence of persistent ductus patency beyond the fourth day of life.…”
Section: Introductionmentioning
confidence: 99%